2010
DOI: 10.1007/s11095-010-0213-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intestinal Precipitation—A Case Example for a Basic BCS Class II Drug

Abstract: This study indicated that simple in vitro methods of in vivo precipitation of orally administered bases overpredict the intestinal crystalline precipitation in vivo in humans. Hydrodynamic conditions were identified as one important factor that needs to be better addressed in future in vivo predictive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
94
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 28 publications
7
94
0
Order By: Relevance
“…Nevertheless, in vivo data relevant to precipitation are almost non-existent. It has recently been shown that intestinal precipitation of a weak base that is under development by AstraZeneca is less of a limitation for in vivo drug absorption than implied from equilibrium solubility and in vitro test assessments (5). Although that was probably the first study dealing with in vivo precipitation/supersaturation of bases, observations were made indirectly (using plasma data), and, therefore, quantitative assessment of the degree of precipitation/supersaturation in vivo was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in vivo data relevant to precipitation are almost non-existent. It has recently been shown that intestinal precipitation of a weak base that is under development by AstraZeneca is less of a limitation for in vivo drug absorption than implied from equilibrium solubility and in vitro test assessments (5). Although that was probably the first study dealing with in vivo precipitation/supersaturation of bases, observations were made indirectly (using plasma data), and, therefore, quantitative assessment of the degree of precipitation/supersaturation in vivo was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…To date, two approaches have been used for predicting lumenal concentrations of weak bases, In the first, concentrations of lipophilic weak bases in the upper small intestine after oral administration in the fasted state have been modelled by combining theoretical particle dissolution and particle growth kinetic models (6,7) or, in the case of administration of liquid dosage forms, by combining nucleation and particle growth models (8), according to the classical theory of crystallization. These approaches have been shown to be useful in forecasting the average plasma profile (7), the cumulative % dose absorbed vs. time plots (6) and the linearity of C max vs.…”
Section: Introductionmentioning
confidence: 99%
“…Dose data (8) in humans. In the second approach, concentrations of lipophilic weak bases in the upper small intestine after oral administration in the fasted state have been modelled using in vitro setups either in the form of single compartment systems (8) or, more frequently, in the form of multiple compartment systems (9)(10)(11)(12). One of these systems has been shown to be useful in forecasting the total % dose absorbed in humans (9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations